A new method for neonatal rat ventricular myocyte purification using superparamagnetic iron oxide particles. (1st November 2018) - Yang, Duomeng; Xi, Junmin; Xing, Yun; Tang, Xiangxu; Dai, Xiaomeng; Li, Kaiying; Li, Hongmei; Lv, Xiuxiu; Lu, Daxiang; Wang, Huadong
Abstract: Background: Neonatal rat ventricular myocytes (NRVMs) have proven to be an ideal research model for cardiac disease. However, the current methods to purify NRVMs have a limitation to obtain high purity. The purpose of this study was to develop a NRVM purification method by using superparamagnetic iron oxide particles (SIOP). Methods: NRVMs were purified by using SIOP (SIOP group). The differential attachment with or without bromodeoxyuridine (BrdU) treatment served as control and BrdU groups, respectively. The Percoll gradient (Percoll) and magnetic–activated cell sorting (MACS) methods were performed to compare the purity and viability of NRVMs with SIOP method. Results: The SIOP group enriched NRVMs up to 93.9 ± 2.0% purity determined by flow cytometry (FCM) and 95.6 ± 1.3% by immunofluorescence count (IF). In contrast, the control group gave purities of 71.9 ± 2.9% (by FCM) and 66.8 ± 8.9% (by IF), and the BrdU group obtained 82.0 ± 1.3% (by FCM) and 83.1 ± 2.4% (by IF). The purity of SIOP-isolated NRVMs was not different from that of Percoll and MACS groups. However, the cardiomyocytes separated by these methods, except SIOP protocol, were mixed with intrinsic cardiac adrenergic cells. NRVMs purified by SIOP shaped the similar three-dimensional morphology, with no difference in cell yield, viability and cytosolic Ca 2+ homeostasis at 24 h after isolation compared with NRVMs in other groups. Furthermore, SIOP-purified NRVMs retained the responses to phenylephrine and lipopolysaccharide challenge. Conclusion: We first reported an efficient and novel method to purify NRVMs using SIOP, which may help accelerate innovative research in the field of cardiomyocyte biology. Graphical abstract: Highlights: Purify neonatal rat cardiomyocytes by superparamagnetic iron oxide particle (SIOP) SIOPs without any antibody conjugated adsorb non-cardiomyocytes completely. SIOPs enrich myocyte purity to >92%, depleting ICA cells, better than other methods. The SIOP method isolates myocytes with good yield, structure, viability and property.